Proniosomal gel-mediated topical delivery of fluconazole: Development, in vitro characterization, and microbiological evaluation - Amal Saber Mohammed Abu El-Enin; Maha Khalifa Ahmed Khalifa; Aya Mohammed Dawaba; Hamdy Mohammed Dawaba (Wolters Kluwer Medknow Publications, 2019)
The aim of this study was to explore the potential of proniosomal gel for topical delivery of fluconazole, an antifungal drug used in fungal infections caused by pathogenic fungi. Fluconazole-loaded proniosomal gels were prepared by the coacervation phase separation method using different nonionic surfactants (spans and tweens). The prepared fluconazole proniosomal gels were evaluated for various parameters such as particle size (PS), drug entrapment efficiency percentage (EE%), and in vitro drug release. The experimental results showed that the EE% for the prepared formulae are acceptable (85.14%-97.66%) and they are nanosized (19.8-50.1 nm) and the diffusion from the gels gave the desired sustaining effect. F4, which was prepared from span 60, tween 80 (1:1), and cholesterol showed highest EE% and gave slow release (40.50% ± 1.50% after 6 h), was subjected to zeta potential (ZP) test, transmission electron microscopy as well as microbiological study. The results showed a well-defined spherical vesicle with sharp boundaries with good physical stability of fluconazole within the prepared gel. Moreover, F4 showed an excellent microbiological activity represented by a greater zone of inhibition (5.3 cm) compared to control gel (fluconazole in 2% hydroxy propyl methyl cellulose (HPMC) gel formula) (4.2 cm) and plain gel with no drug (0 cm) against Candida albicans. This study showed the suitability of the proniosomal gel in attaining the desired sustainment effect for topical delivery of fluconazole for the management of fungal infection. The physical stability study showed that there was no significant change in EE%, PS, and ZP of fluconazole proniosomal gel after storage for 6 months.